2017
DOI: 10.1039/c7ra00267j
|View full text |Cite
|
Sign up to set email alerts
|

Facile construction of a polydopamine-based hydrophobic surface for protection of metals against corrosion

Abstract: Metal surfaces with a hydrophobic feature, which could prevent percolation of water droplets and improve their capability against corrosion, arouse extensively interest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 48 publications
1
14
0
3
Order By: Relevance
“…1Ci), corresponding to the CH 2 stretching of the 1-DT long alkyl chain. 49,50 The iron oxide MNPs were identified by X-ray diffraction (XRD) as magnetite (Fe 3 O 4 ) with a crystallite size of 7.4 ± 0.5 nm (see the ESI, Fig. S2 and Table S1 †), and the content of the magnetic material adsorbed onto the CNCs was estimated to be 32.4 wt% by thermogravimetric analysis (TGA; see the ESI, Fig.…”
Section: Production and Characterization Of Magnetic Nanoparticlesmentioning
confidence: 99%
“…1Ci), corresponding to the CH 2 stretching of the 1-DT long alkyl chain. 49,50 The iron oxide MNPs were identified by X-ray diffraction (XRD) as magnetite (Fe 3 O 4 ) with a crystallite size of 7.4 ± 0.5 nm (see the ESI, Fig. S2 and Table S1 †), and the content of the magnetic material adsorbed onto the CNCs was estimated to be 32.4 wt% by thermogravimetric analysis (TGA; see the ESI, Fig.…”
Section: Production and Characterization Of Magnetic Nanoparticlesmentioning
confidence: 99%
“…It can be also seen from the SEM images that the PDA-coated CNTs can aggregate more than bare CNTs. It was reported that there was an increase in the hydrophobicity of CNT after PDA coating, and the increased hydrophobicity and aggregation enabled the utilization of PDA-coated materials' new properties e.g., preventing corrosion and so on [43,52,53].…”
Section: Multiple Pda Coating On Cntsmentioning
confidence: 99%
“…This surface modification process is inspired by the adhesion approach carried out by invertebrate mussels to fix onto different substrates, wet or dry, with high binding strength. This bioinspired mussel adhesive mechanism has potential for application in several areas, 32 mainly in materials science 31,33–36 …”
Section: Introductionmentioning
confidence: 99%
“…This bioinspired mussel adhesive mechanism has potential for application in several areas, 32 mainly in materials science. 31,[33][34][35][36] The rheology is essential to simulate the processing of polymer and polymeric composites (melts, solutions, or suspensions) to achieve products with suitable properties and dimensions. This science enables us to model the flow and deformation of polymeric melts mathematically under shear stress and shear strains over time.…”
Section: Introductionmentioning
confidence: 99%